Ideen einer aufklärerischen Gesangbuchkonzeption - Grube, Heinz-Hermann (Jahrbuch für Liturgik und Hymnologie, 1989)
The essay tries a new estimation concerning the creation of hymns during the age of enlightenment. It originates from the efforts of Friedrich Gottlieb Klopstock for creating or altering hymns. His intention was a specific mediation of poetic possibilities with the situation of a religious congregation. At first Klopstock comes to a determination of the function of a hymn: it must "touch hearts". Thus it is indicated that hymns had an important function during the total process of enlightenment: they were a kind of position of switch in the ecclesiastical enlightenment. Through hymns – while touching the congregation – the heard truth was to enter into one's feelings. By awakening emotions the congregation was to be led to an appropriate action. Therefore the strong emphasis of emotions is to be understood as a necessary correlate for rational efforts in the process of enlightenment. Reflecting this, Klopstock tries to determine attributes of hymns such as clearness, full of "soft devotion". Concerning the essence, Klopstock wants to be in harmony with the biblical truth. However, reflecting upon the creation of hymns during the era of enlightenment, the term of felicity plays a far more important part. The consciousness that men are on different stages within the process of enlightenment justifies the pedagogical disposition of the enlightenment altogether. Whoever posesses the privilege of knowing the truth, also has the duty of transmitting it with the indicated means. The reproach, that the enlightenment had thrown over board all earlier creations, must be relativated by the fact that at the time of enlightenment one believed to act without responsibility if one did not create new songs and improve old hymns in order to lead everyone to the aim of real "enlightenment".